Profile of Religiosity, Spirituality, Emotional Regulation, and Mental Health in Adolescents - Nia Agustiningsih; Faizatur Rohmi; Listiyawati Ratnaningrum (Journal Of Nursing Practice, 2026)
Background: Religiosity, spirituality, and emotional regulation are some of the factors that contribute to adolescent mental health. Purpose: The purpose of this study is to describe the profile of religiosity, spirituality, emotional regulation, and mental health of adolescents. Methods: This research is a quantitative descriptive study with a cross-sectional approach. The sample of the study was 184 adolescents in high school who met the criteria, which was carried out by purposive sampling. Researchers adapted and modified questionnaires, namely the Daily Spiritual Experience Scale, Duke University Religion Index, Emotion Regulation Scale, and Mental Health Inventory. Data were analyzed descriptively and presented in frequency distribution, percentage, minimum, maximum, average, and standard deviation using SPSS. The study has been declared ethically appropriate with number 750/S.Ket/KEPK/UK/X/2025. Results: The results of the study obtained data that of the 184 adolescents, most were in the moderate category, namely religiosity 144 people (78.3%), spirituality 112 people (60.9%), emotional regulation 133 people (72.3%), and adolescent mental health 133 people (72.3%). Conclusion: Religiosity, spirituality, emotional regulation, and mental health in adolescents are important aspects that nurses must pay attention to as providers of comprehensive nursing care that includes bio-psycho-socio-spiritual aspects.